PERAN PEMUDA DALAM MENYUKSESKAN PEMILU DI DESA TERUSAN KECAMATAN BATURAJA TIMUR KABUPATEN OGAN KOMERING ULU: THE ROLE OF YOUTH IN THE SUCCESS OF ELECTIONS IN CANAL VILLAGE, EAST BATURAJA DISTRICT, OGAN KOMERING ULU REGENCY - Herwin Sagita Bela; Hanny Saykarua; Alya Sifa Perdani; Milki Lubis; Kaka Adhe Mahendra Putra; Yana Riyani (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Youth participation during general elections in democratic countries still cannot be said to be high, this is influenced by the factor of many young people who miss at the time of general elections. One of the efforts to reduce it is by holding political education socialization and general elections to the public and youth in particular as prospective novice voters for the 2024 election, in order to reduce the number of abstentions and make youth smarter in elections and understand the role of youth in the success of the upcoming 2024 elections. The holding of political socialization so that youth not only become political objects but become political subjects. Therefore, the Government Science Study Program, Faculty of Social and Political Sciences, Baturaja University conducts service on political education and elections to welcome the 2024 election in Canal Village, East Baturaja District, Ogan Komering Ulu Regency. The entire stage was carried out well as expected.